UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN MINAT BERSEKOLAH BAGI CALON PESERTA DIDIK BARU DI SMPIT AL-RIDWAN - Lukmanul Hakim Ramdhani; Sya'roni Ma'shum; Saprialman Saprialman (STAI Ihyaul Ulum Gresik, 2025)
This study aims to find out how the school principal's efforts in dealing with competition to recruit new students, the research method used is descriptive qualitative research. The role of the school principal as a leader in an existing education unit is required to carry out various innovations with various adjustments, in accordance with existing needs and all careful planning. The mushrooming of educational institutions that have been established has made many choices for new students to go to school, the principal should be able to anticipate all of this, so there must be an effort made by the principal to win the hearts of these prospective new students, by having a promotion strategy. which is good, cooperation with other parties or others.